2021
DOI: 10.1021/acs.jpca.1c00739
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism of Near-Infrared Thermally Activated Delayed Fluorescence of TPA-Based Molecules: Effect of Hydrogen Bond Steric Hindrance

Abstract: A recently synthesized novel molecule (named CAT-1) exhibits intriguing near-infrared (NIR) thermally activated delayed fluorescence (TADF) close to 1000 nm wavelength; however, the mechanism behind these intrinsic properties is not fully understood. Herein, we unravel that the fluorescence emission spectrum with a broad wavelength range (770–950 nm) of CAT-1 is primarily induced by hydrogen bond steric hindrance based on density functional theory and Marcus theory. It is found that the hydrogen bond steric hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…This implies that as the strength of donating and accepting moieties increases, leading to more effective π electron transfer in conjugated systems, the HOMO–LUMO gaps (E g ) decreases [80–82] . Thus, reducing ΔE ST is achieved by using strong donor and acceptor units [83,84] . Furthermore, the electron donating and accepting ability of D and A groups do not only affect ΔE ST , but they also have an important role in tuning the emission color of TADF emitters [85] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that as the strength of donating and accepting moieties increases, leading to more effective π electron transfer in conjugated systems, the HOMO–LUMO gaps (E g ) decreases [80–82] . Thus, reducing ΔE ST is achieved by using strong donor and acceptor units [83,84] . Furthermore, the electron donating and accepting ability of D and A groups do not only affect ΔE ST , but they also have an important role in tuning the emission color of TADF emitters [85] .…”
Section: Resultsmentioning
confidence: 99%
“…[80][81][82] Thus, reducing ΔE ST is achieved by using strong donor and acceptor units. [83,84] Furthermore, the electron donating and accepting ability of D and A groups do not only affect ΔE ST , but they also have an important role in tuning the emission color of TADF emitters. [85] The experimental emission wavelengths are reported in SI showing that the molecules covers efficiently the blue and green portion of the electromagnetic spectrum.…”
Section: Donor-acceptor Strengthsmentioning
confidence: 99%
“…[71][72][73] Thus, reducing ΔEST is achieved by using strong donor and acceptor units. 74,75 Furthermore, the electron donating and accepting ability of D and A groups do not only affect ΔEST but they also have an important role in tuning the emission color of TADF emitters. 76 In our molecular set, we benefited from the electron accepting ability of boron atom and we have analyzed its effect on hole orbitals.…”
Section: Donor -Acceptor Strengthsmentioning
confidence: 99%
“…2 ) has recently been reported to lie in the use of intramolecular hydrogen bonds to fixate the relative positions and rotations of charge-transfer (CT) donor and acceptor units. 6 In comparing CAT-1 with its non hydrogen-bonded counterpart TPAAP, 7 (3-(4-(diphenylamino)phenyl)acenaphtho[1,2- b ]pyrazine-8,9-dicarbonitrile) Leng et al found a lowered λ int that may be responsible for its more efficient NIR-TADF process compared to TPAAP.…”
Section: Introductionmentioning
confidence: 99%